1988
DOI: 10.1172/jci113439
|View full text |Cite
|
Sign up to set email alerts
|

Vascular transport of insulin to rat cardiac muscle. Central role of the capillary endothelium.

Abstract: Using intact, beating hearts, we have assessed the interaction of insulin with capillary endothelium and the subsequent appearance of insulin in cardiac muscle. Rat hearts were perfused with '25I-insulin (10`0 M) alone or in combination with unlabeled insulin (10-9-10-5 M). 125I grains (shown to represent > 90% intact insulin) over both capillary endothelium and cardiac muscle decreased in a dose-dependent manner when hearts were co-perfused with labeled insulin and increasing concentrations of unlabeled insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…This would certainly be consistent with the early observations by King and Johnson (12) that insulin transport displayed saturable kinetics and was inhibited by anti-IR antibodies in cultured endothelial cells. Likewise, in the more physiological setting of the perfused rat heart, when insulin was added to the perfusate at a range of insulin concentrations from Ͻ10 Ϫ10 to ϳ10 Ϫ5 M, the higher concentration of insulin diminished the amount of 125 I-insulin detected in autoradiographs over endothelial cells and muscle interstitium, suggesting saturation kinetics of insulin transport (1). In addition to IR, endothelial cells possess abundant IGF-IR that bind insulin at concentrations in the nanomolar range (5, 13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would certainly be consistent with the early observations by King and Johnson (12) that insulin transport displayed saturable kinetics and was inhibited by anti-IR antibodies in cultured endothelial cells. Likewise, in the more physiological setting of the perfused rat heart, when insulin was added to the perfusate at a range of insulin concentrations from Ͻ10 Ϫ10 to ϳ10 Ϫ5 M, the higher concentration of insulin diminished the amount of 125 I-insulin detected in autoradiographs over endothelial cells and muscle interstitium, suggesting saturation kinetics of insulin transport (1). In addition to IR, endothelial cells possess abundant IGF-IR that bind insulin at concentrations in the nanomolar range (5, 13).…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of previous studies examining the time course for insulin entry into the endothelial cell or the anatomic pathway by which insulin exits the vasculature within skeletal muscle. Bar et al (1) observed that within 2 min after adding 125 I-labeled insulin to the perfusate of an isolated rat heart, the endothelial cells and subsequently cardiac muscle interstitium were labeled. Interestingly, in that study, in addition to observing a rapid uptake of 125 I-insulin by the endothelial cell, the investigators also reported that the intensity of labeling of the endothelial cell was Ͼ10-fold above that of muscle interstitium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain why the glucose disposal rate is closely correlated with insulin kinetics in the interstitial fluid but only loosely with changes in insulin plasma concentrations [34]. Moreover, transfer of low affinity insulin analogues from the blood stream to muscle tissue in situ is significantly impaired as is insulin processing in the presence of anti-IR antibodies against endothelial IR [13]. Further indications of a receptor-mediated insulin passage across the endothelium have been provided by human studies, where two distinctly different methods have revealed a saturating effect on insulin transport into the interstitial space when increasing infused insulin concentrations [8,35].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, differences in the expression of caveolae associated ligand-binding receptors involved in protein endocytosis have been proposed as an indicator of the exchange efficiency of macromolecules across the endothelium [11]. Evidence supporting the notion that transendothelial insulin processing is receptor-mediated is, firstly, unidirectional insulin transport is inhibited by anti-insulin receptor (IR) antibodies in vitro and in situ [12,13]. Secondly, serine and tyrosine phosphorylation of the IR b-subunit has been shown to increase both internalization and externalization of insulin in vitro, suggesting a role for IR activation and phosphorylation in insulin transport [14].…”
mentioning
confidence: 99%